Induced Seismicity in Western Canada Linked to Tectonic Strain Rate: Implications for Regional Seismic Hazard. Issue 20 (29th October 2018) - Kao, Honn; Hyndman, Roy; Jiang, Yan; Visser, Ryan; Smith, Brindley; Babaie Mahani, Alireza; Leonard, Lucinda; Ghofrani, Hadi; He, Jiangheng
Abstract: A rapid increase of injection‐induced earthquakes (IIE) is often linked to a higher level of seismic hazard. In this study, we compare the geodetically defined moment rate to seismicity distribution in western Canada where significant IIE are observed. The regional seismic pattern is dominated by IIE, both in number and moment, along a 150‐km wide NW‐SE band of moderate strain rate in the easternmost Cordillera and foothills. The observed rate of moment release from local earthquakes is much closer to the tectonic moment rate in the IIE‐dominated areas. We conclude that, on a regional scale, tectonic strain rate is an important control on IIE. Injection in areas with moderate tectonic strain may temporarily increase the local seismic hazard, but widespread IIE over an extended period of time may deplete the available tectonic moment and could, under the right conditions, have a limited long‐term effect of reducing regional seismic hazard. Plain Language Summary: Fluids are commonly injected into oil and gas wells to shutter the reservoir formations of shale gas and tight oil and to increase production. However, not all injections cause induced earthquakes and some areas have more events than others. In this study, we examine the geological controls on where there is greatest susceptibility to induced earthquakes. In western Canada, we find that they are generally associated with the areas of moderate long‐term geological/tectonic deformation rates, as mapped by the relative motion of high‐resolution Global Navigation Satellite System stations. Most induced earthquakes are in a 150‐km‐wide band in the easternmost Canadian Cordillera and foothills. They are much less frequent farther to the east where the geological deformation rates are low. We conclude that the geological deformation rate is an important controlling factor for the occurrence of induced earthquakes. In some areas, the strain rate from induced earthquakes may temporarily exceed the natural geological strain rate. Widespread injections in areas with relatively high geological deformation rate may increase the regional seismic hazard in the short term. But if frequent occurrence of induced earthquakes persists over time, it could lead to a reduction of natural earthquake occurrence in the long term. Key Points: Most induced seismicity in western Canada occurred in regions with relatively higher tectonic strain rate Release rate of seismic moment in the most active areas of induced seismicity exceeds the corresponding tectonic moment rate Injections may temporarily increase the local seismic hazard, but widespread induced seismicity may have a contrasting long‐term effect